Study of Seepage Coefficient of Trapezoidal Cross-Section Irrigation Channel on Latosol Soil at Laboratory Scale - Ayu Wulandari; Sumono Sumono; Achwil Putra Munir (Jurnal Rekayasa Pangan dan Pertanian, 2016)
Seepage is one of the causes of lost of water in irrigation channel. It is difficult to measure the seepage directly on the field. Therefore there should be a model or equation to determine the channel seepage that is the first stage through laboratory scale. This research was done to analyze the seepage coefficient of trapezoidal cross-section irrigation channel on Latosol soil through laboratory scale. The water balance component which was measured were evaporation, percolation and seepage through channel wall. The research showed that the coefficient of seepage was about 3732,48 to 5339,52 mm/day. The evaporation  value was 1,33 mm/day and channel percolation was 376,41mm/day. Key Word : coefficient of seepage, irrigation channel, trapezoidal cross-section, Latosol soil, laboratory scale.